Mediators of Behavior Change Maintenance in Physical Activity Interventions for Young and Middle-Aged Adults: A Systematic Review. Issue 6 (17th April 2018) - Murray, Jennifer M; Brennan, Sarah F; French, David P; Patterson, Christopher C; Kee, Frank; Hunter, Ruth F
Abstract: Background: Regular physical activity is important for maintaining physical and mental health. Benefits are optimized when physical activity is maintained. Understanding causal mechanisms is important to inform future interventions. Purpose: To investigate mediators of physical activity maintenance. Methods: Six databases were searched (Medline, EMBASE, PsycINFO, CINAHL, Cochrane Database of Systematic Reviews, and Web of Science). Eligibility criteria included adult nonclinical populations, validated measure of physical activity behavior at baseline and at least 6 months postbaseline, control/comparison group(s), and reported mediators of physical activity behavior change. Mediators were examined according to (i) formal mediation tests, (ii) mediator association with physical activity outcome, and (iii) intervention effects on mediators. Results: There were few formal mediation tests conducted ( n = 12/39 included studies), and various other methodological limitations were identified. There was some evidence that effective mediators in formal mediation tests at 6 months and later included the "behavioral processes of change" ( n = 5/6). Many of the included interventions were not effective for changing targeted mediators (only 34% of 413 tests of mediator changes were significant). Conclusions: There were a number of methodological and statistical limitations in the evidence base. In future, prespecified formal mediation tests should be carried out and could be aided by a formal framework. Social and environmental variables should be considered in addition to intrapersonal variables. Improving knowledge of how to change hypothesized mediators, based on theory and evidence, will reveal how physical activity behavior change maintenance can be achieved. Maintenance research would be enhanced by establishing a formal definition of behavior change "maintenance." PROSPERO registration : PROSPERO 2015:CRD- 42015025462 Abstract : This literature review highlights how little we know about what psychological, social or environmental factors help adults be active long-term.